Peran Kurkumin Sebagai Pengembangan Terapi Untuk Otitis Media Akut - Agtara Liza Asthri (MAJORITY, 2020)
Acute Otitis Media (AOM) is an inflammation of the middle ear that lasts less than three weeks (acute) accompanied by local and systemic symptoms. The highest prevalence of AOM in West and Central Africa (43.37%). The prevalence of AOM in Indonesia in 2013 found that the most AOM were in the toddlers group (40.4%), boys (52%), children with parent jobs housewives (48.1%). The causes are aerobic bacteria such as Streptococus aures, Pneumococci, Hemolyticus influenza, and Pseudomonas aeruginosa. AOM treatment uses antibiotics and anti-inflammatory drugs. However, currently the role of curcumin is being developed as an anti-inflammatory of AOM. Curcumin (Diferuloylmethane), the orange-yellow component of turmeric which is a natural polyphenol product isolated from the rhizome of the Curcuma longa plant. In recent years, extensive in vitro and in vivo research has shown that curcumin has anticancer, antiviral, antiarthritic, antiamyloid, antioxidant, and anti-inflammatory. The use of curcumin against otitis media in suppressing the inflammatory process and repairing the damaged tissue structure. In addition, curcumin has the ability to weaken Pseudomonas aeruginosa biofilm formation and inhibit angiogenesis and also reduce the expression of various proangiogenic growth factors, such as vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF), and epidermal growth factor.